Grammar and Translation - GRDZELYAN, ROUZAN (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is devotedto the problem of the correlation between grammar and translation. Within the framework of linguistics, the language can be viewed from different points of view - from the point of view of theoretical, comparative and functional grammars, etc. The purpose of this study is to determine the boundaries and functions of transferable grammar.